DEPUTY OF DEPARTMENT STRATEGIC PLANNING AND SIMPLIFICATION OF CUSTOMS PROCEDURES (Intent Research Scientific Journal, 2024)
This article examines Uzbekistan's progress in trade facilitation reforms and its implications for economic growth and integration into global markets. The purpose of the paper is to analyze Uzbekistan's efforts to streamline customs procedures, digitize trade processes, and align with WTO standards to enhance its international trade landscape. The author indicates key initiatives (“Single Window” system and “Uzbekistan Trade Info”), which have collectively improved its trade facilitation score from 20.43% in 2015 to 84.95% in 2023. These measures aim to reduce trade costs, foster foreign investment, and position Uzbekistan as a strategic trade hub within Central Asia. This article also discusses the prospective impact of the upcoming Action Plan for 2024-2025, aimed at achieving full WTO compliance by 2025, and highlights the ongoing regulatory and technological developments necessary for fostering a competitive and efficient trade environment.